The Role of Social Media and Information Technology in Emergency Mitigation to Increase the Knowledge of Coastal Communities - Sonata Togatorop; Tinawati Nainggolan; Septi Septi; Pretty Pretty (Institute Of Computer Science (IOCS), 2025)
This study aims to analyze the role of social media and information technology in increasing public knowledge about emergency mitigation in the coastal area of ??Pasir Lapangan Village in 2025. The study used a quantitative method with a one-group pretest-posttest design. A sample of 200 respondents was selected using a cluster sampling technique. Data were collected through questionnaires before and after an educational intervention through social media. The results showed that before the intervention, most respondents had a low level of knowledge (44%), while after the intervention it increased to a good category (59%). The results of the statistical test showed a p-value = 0.001 (<0.05), which means there is a significant effect of social media use on increasing public knowledge. The conclusion of this study is that social media is effective as a means of emergency mitigation education and can increase coastal community preparedness for disasters